Effects of cue modality and emotional category on recognition of nonverbal emotional signals in schizophrenia. Issue 1 (December 2016) - Vogel, Bastian; Brück, Carolin; Jacob, Heike; Eberle, Mark; Wildgruber, Dirk
Abstract Background Impaired interpretation of nonverbal emotional cues in patients with schizophrenia has been reported in several studies and a clinical relevance of these deficits for social functioning has been assumed. However, it is unclear to what extent the impairments depend on specific emotions or specific channels of nonverbal communication. Methods Here, the effect of cue modality and emotional categories on accuracy of emotion recognition was evaluated in 21 patients with schizophrenia and compared to a healthy control group (n  = 21). To this end, dynamic stimuli comprising speakers of both genders in three different sensory modalities (auditory, visual and audiovisual) and five emotional categories (happy, alluring, neutral, angry and disgusted) were used. Results Patients with schizophrenia were found to be impaired in emotion recognition in comparison to the control group across all stimuli. Considering specific emotions more severe deficits were revealed in the recognition of alluring stimuli and less severe deficits in the recognition of disgusted stimuli as compared to all other emotions. Regarding cue modality the extent of the impairment in emotional recognition did not significantly differ between auditory and visual cues across all emotional categories. However, patients with schizophrenia showed significantly more severe disturbances for vocal as compared to facial cues when sexual interest is expressed (alluring stimuli), whereas more severe disturbances for facial as compared to vocal cues were observed when happiness or anger is expressed. Conclusion Our results confirmed that perceptual impairments can be observed for vocal as well as facial cues conveying various social and emotional connotations. The observed differences in severity of impairments with most severe deficits for alluring expressions might be related to specific difficulties in recognizing the complex social emotional information of interpersonal intentions as compared to "basic" emotional states. Therefore, future studies evaluating perception of nonverbal cues should consider a broader range of social and emotional signals beyond basic emotions including attitudes and interpersonal intentions. Identifying specific domains of social perception particularly prone for misunderstandings in patients with schizophrenia might allow for a refinement of interventions aiming at improving social functioning.